Hey There!
We have been given:
![8x + 3y = 13 \\ 3x + 2y = 11](https://img.qammunity.org/2020/formulas/mathematics/middle-school/a0esjq1aktax77qkcs3962lw77srfgp6yn.png)
Find the lcm of 3 and 2 to eliminate one equation:
3 * 2 = 6
2 * 3 = 6
Multiply each equation to get to 6:
![2(8x + 3y = 13)\\ 16x + 6y = 26](https://img.qammunity.org/2020/formulas/mathematics/middle-school/8huqwkpf59s0whibfvdo0mh7nz8mihui5l.png)
![3(3x + 2y = 11)\\ 9x+6y=33](https://img.qammunity.org/2020/formulas/mathematics/middle-school/ph93xpid1lb5k8c0fsc03ah4e0o1qyut5i.png)
Eliminate:
![16x + 6y = 26\\ -(9x+6y=33)\\ -9x - 6y=-33](https://img.qammunity.org/2020/formulas/mathematics/middle-school/6jzazvp1d52zx1vt9u6dx84qlgehe8nkwn.png)
Simplify:
![16x + 6y = 26\\ -9x - 6y=-33 \\ 7x = -7](https://img.qammunity.org/2020/formulas/mathematics/middle-school/zrs1rzwpcol2sceda0fbk752g465hnmajm.png)
Solve for x by dividing 7 in both sides:
![7x = -7\\ x = -1](https://img.qammunity.org/2020/formulas/mathematics/middle-school/1x0raosq3o280zhn686dmme9m0ixjbieil.png)
Solve for y by substituting x in any equation with -1:
![8(-1) + 3y = 13](https://img.qammunity.org/2020/formulas/mathematics/middle-school/e7fdm40h1dav4b3ifu2knsmn9rvs9ittiv.png)
Simplify:
![-8 + 3y = 13](https://img.qammunity.org/2020/formulas/mathematics/middle-school/qqw4egs5zbwwvo2srwh4anrotpeda8477b.png)
Add 8 in both sides:
![3y = 21](https://img.qammunity.org/2020/formulas/mathematics/middle-school/mkyt3uuoz222t4r65yyxwip95b17s458ps.png)
Solve for y by dividing 3 in both sides:
![y = 7](https://img.qammunity.org/2020/formulas/mathematics/middle-school/oojko1o2vxbdmg4t293uh3lnwepfu5w6il.png)
The value of x is -1 and the value of y is 7
Our answers:
x = -1
y = 7